Empowering Creative Economic Centers in Gebyok Crafts for The Conservation of Local Culture, A Superior Product in Kudus Regency - Nur Fajrie; Gilang Puspita Rini; Muhammad Sholikhan; Slamet Khoeron; Hisbulloh Als Mustofa (Yayasan Keluarga Guru Mandiri, 2025)
Kudus Gebyok crafts, a significant intangible cultural heritage, face threats from artisan regeneration issues, traditional production inefficiencies, and limited market reach. This study aims to empower the Gebyok Creative Economy Center by integrating technological innovation and digitalization to ensure cultural conservation. A participatory action research approach was employed with two artisan partners, involving the modernization of production tools, training in digital motif design, registration of Intellectual Property Rights (IPR), and development of digital marketing strategies. The results demonstrated significant improvements, with the adoption of modern machinery increasing production efficiency by up to 81.56%. Additionally, five distinctive motifs were successfully digitized and legally protected through IPR registration, and market access was expanded through the creation of social media channels and an e-catalog. In conclusion, the strategic implementation of technology and digitalization proved effective in enhancing production capacity while safeguarding cultural assets. This research contributes a replicable empowerment model for other heritage-based creative industries, demonstrating a viable pathway to synergize cultural preservation with economic sustainability in the modern era.